Investigation of maternal breastfeeding guarantee policy needs and influencing factors: a cross-sectional study in China - Li, Junying; Zhang, Lan; Guo, Nafei; Liu, Ying; Jiang, Hui (Frontiers in Health Services, 2024)
Background The promotion of breastfeeding is an important strategy to prevent neonatal death and improve maternal and infant health. But Chinese efforts to improve breastfeeding practices have not been particularly effective. There is still a long way to go to achieve the national health development goals. We aimed to explore the maternal demand for breastfeeding guarantee policy in China and to determine the impact of a range of socio-demographic and neonatal-related variables on breastfeeding guarantee policy demand. Methods The study was carried out in the Obstetrics and Gynecology hospital of Shanghai, one of China's earliest provincial and municipal maternal and child health care institutions. From June to November 2021, 1,292 women were recruited for the cross-sectional study in child health clinic. We collected relevant socio- demographic and neonatal-related data. Maternal breastfeeding needs were measured through a self-designed questionnaire on breastfeeding guarantee policy demands of mothers. Results The mean score of breastfeeding guarantee policy demand was 4.42 ± 0.51. There were statistically significant differences in the effects of maternal age, education level, family income per capita (Yuan), medical payment type, baby age, work status, and current feeding methods on the demand for breastfeeding guarantee policies (P < 0.05). Multiple linear regression analyses showed that higher education level (B = 4.437, P < 0.001), baby age (B = 2.150, P = 0.002), and current feeding methods (B = 2.754, P = 0.005) were significantly associated with a higher demand for a breastfeeding guarantee policy, the effect of medical payment type is the most influencing factor (B = −7.369, P < 0.001). Conclusions The maternal needs for breastfeeding guarantee policy are multi-faceted and urgent. In the process of improving and implementing policies, the government and relevant departments should take into account the actual needs of women who have different education levels, baby ages, family economics, and feeding methods.